Ye. Oʻsmir yoshdagi oʻquvchilarda kreativ fikrlashni rivojlantirish psixodiagnostikasi - Djolımbetova, M.M; Aytmuratova, E (SCIENCE and SOCIETY, 2025)
In this state, information is presented about the psychological characteristics of pre-adolescence, mental development and independent thinking, creative thinking, intelligence, mainly studying the meaning of creativity in various
Keywords: adolescence; creativity; psychological development; creative thinking; social creativity; independent thinking; intellectuality